Peran manajemen strategis dalam membangun kepercayaan dan loyalitas nasabah pada bank syariah - Ahmad, Reki (Maliki Interdisciplinary Journal, 2025)
This article discusses the role of strategic management in building customer trust and loyalty in Islamic banks in Indonesia. Amidst the rapidly growing Islamic banking industry, a key challenge is the development and implementation of Sharia-compliant management strategies, such as fairness, transparency, and Islamic business ethics. This article demonstrates the importance of improving service quality by leveraging digital technology and implementing a customer relationship management (CRM) system to enhance customer loyalty. A case study of Bank Mandiri Syariah demonstrates how combining Sharia principles and strategic innovation can enhance customer trust and loyalty while addressing dynamic market competition. In short, the sustainability and competitiveness of Islamic banks in the modern era depend on strategic management focused on Sharia values.